Use of Mycorrhiza as Environmental Social Responsibility: The Case of Melon Cultivation and Marketing in ValleduparUse of Mycorrhiza as Environmental Social Responsibility: The Case of Melon Cultivation and Marketing in Valledupar - Mendoza, Jose Ricardo Rois; Farelo, Greicy Liliana Ospino; Pacheco, César Alfonso Manjarrez Ponton; Galindo, Diana Carolina Garcia; Mejía, Sabas Antonio Vega; Sanchez, Juan Carlos Valdivieso; Fonseca, Yeison Enrique Maestre (Journal of Posthumanism, 2025)
In this study, the effect of mycorrhiza in a commercial melon crop in the township of Guacoche, Valledupar, Cesar, was evaluated within the framework of the environmental social responsibility work of the Popular University of Cesar. A plot design divided into random blocks was used, where the first factor was the dose of mycorrhiza (0, 5, 10, 20 and 40 g/10 kg of soil), and five mycorrhizal plots and four controls were established, in addition to five replications. The second factor was the crop sampling cycle (10, 20 and 30 days, plus 10 days after harvest). For the collection of the variable number of leaves, two plants were taken at random from each subsample, classified into two types according to their morphology, each representing a cycle of melon crops; Two subsamples containing 100 g of soil with strictly measured diatized water were used to analyze six elements.